An Introduction to Derivatives and Risk Management - Chance, Don M. and Brooks Robert (Mason, OH Thomson/South-Western, 2007)
You'll find detailed but flexible coverage of options, futures, forwards, swaps, and risk management as well as a solid introduction to pricing, trading, and strategy in AN INTRODUCTION TO DERIVATIVES AND RISK MANAGEMENT. A collection of figures illustrate links between puts, calls, stocks, risk-free bonds, futures, options, forwards, Black-Scholes call/put pricing, etc. Included with your purchase is a StockTrack Coupon.
Includes Glossary and Index.
Keywords: Risk management